2006
DOI: 10.1186/1472-6904-6-6
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of the solvent vehicle sulphobutylether beta cyclodextrin sodium in critically ill patients treated with intravenous voriconazole under renal replacement therapy

Abstract: Background: Voriconazole was introduced for the treatment of life-threatening fungal infections. The intravenous form includes the solvent vehicle sulphobutylether beta cyclodextrin sodium which shows an impaired clearance under intermittent dialysis therapy. This investigation aimed to determine first clinical data on sulphobutylether beta cyclodextrin sodium blood levels to verify the risk for accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 11 publications
2
38
1
Order By: Relevance
“…This may be explained by differences in membrane material and surface area of the applied dialyzer as well as by differences in blood, dialysate, and ultrafiltrate flow rates. The extensive clearance observed in our study appears to be contradictory to the recent study of von Mach and coworkers (19) who observed a considerable increase of SBECD in four critically ill patients despite intermittent dialysis. In three of these patients, plasma SBECD concentrations of up to 580 mg/liter were observed.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This may be explained by differences in membrane material and surface area of the applied dialyzer as well as by differences in blood, dialysate, and ultrafiltrate flow rates. The extensive clearance observed in our study appears to be contradictory to the recent study of von Mach and coworkers (19) who observed a considerable increase of SBECD in four critically ill patients despite intermittent dialysis. In three of these patients, plasma SBECD concentrations of up to 580 mg/liter were observed.…”
Section: Discussioncontrasting
confidence: 56%
“…In three of these patients, plasma SBECD concentrations of up to 580 mg/liter were observed. In one of these patients, in whom concentrations were measured before and after dialysis on the same day, the SBECD concentration was only 3% lower after hemodialysis (19), indicating negligible elimination. The apparent discrepancy between this data and our data is likely due to the use of low-flux filter membranes (cutoff approximately 1,000 Da) by von Mach and high-flux filter membranes (cutoff approximately 20,000 Da) in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on patients with impaired renal function is scarce. Three small studies on critically ill patients requiring hemodialysis showed accumulation of SBECD over time without observation of any toxic effects (3,4,10).…”
mentioning
confidence: 99%
“…However, caution should be exercised when IV voriconazole is used in patients with a creatinine clearance (CrCl) 550 mL/min or with IV itraconazole in patients with CrCl 530 mL/ min 7 . This is because the cyclodextrin component of these parenteral formulations can accumulate in patients with renal disease, and some animal studies suggest very high cyclodextrin may be associated with renal toxicity 58 . Voriconazole dose reduction is recommendations for patients with mild-to-moderate hepatic dysfunction 59 .…”
Section: Pharmacokinetics (Pk) and Therapeutic Drug Monitoring (Tdm)mentioning
confidence: 99%